2017
DOI: 10.1111/1462-2920.13861
|View full text |Cite
|
Sign up to set email alerts
|

Dual RNA‐Seq of Lysobacter capsici AZ78 – Phytophthora infestans interaction shows the implementation of attack strategies by the bacterium and unsuccessful oomycete defense responses

Abstract: Biological interactions in the microbial communities of the rhizosphere continuously shape the gene expression patterns of each individual microorganism. A dual RNA-Seq approach was applied to obtain a comprehensive overview of the molecular mechanisms activated during the interaction between the biocontrol rhizobacterium Lysobacter capsici AZ78 and the soilborne phytopathogenic oomycete Phytophthora infestans. The RNA-Seq transcriptional profile of L. capsici AZ78 was characterized by up-regulation of genes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 90 publications
0
32
0
Order By: Relevance
“…The attempted cellular responses of P. infestans against tagatose included the upregulation of maai, which is homologous to gst genes commonly upregulated by oxidative stresses (Montibus et al, 2015). The maai gene is a marker of stress responses and its expression was also upregulated by the biocontrol agent Lysobacter capsici AZ78 in P. infestans (Tomada et al, 2017) and by copper sulfate in Saprolegnia parasitica (Hu et al, 2016). In addition, tagatose upregulated the expression of aif in P. infestans and it encoded a protein involved in ROS scavenging (Klein et al, 2002) and mitochondrial cristae regulation (Cheung et al, 2006) in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…The attempted cellular responses of P. infestans against tagatose included the upregulation of maai, which is homologous to gst genes commonly upregulated by oxidative stresses (Montibus et al, 2015). The maai gene is a marker of stress responses and its expression was also upregulated by the biocontrol agent Lysobacter capsici AZ78 in P. infestans (Tomada et al, 2017) and by copper sulfate in Saprolegnia parasitica (Hu et al, 2016). In addition, tagatose upregulated the expression of aif in P. infestans and it encoded a protein involved in ROS scavenging (Klein et al, 2002) and mitochondrial cristae regulation (Cheung et al, 2006) in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, literature is generally lacking data regarding the effect of co-culture with other microorganisms in general and A. flavus in particular. Other transcriptional studies have reported various responses of both fungi and bacteria depending on the interacting partners [62][63][64]. These responses may promote different biological outcomes ranging from antagonism to cooperation [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Lysobacter spp. may control phytopathogenic microorganisms using several other modes of actions such as lytic enzymes and by the ability to prey upon phytopathogenic microorganisms (Nakayama et al, 1999;Folman et al, 2004;Tomada et al, 2017).…”
Section: Introductionmentioning
confidence: 99%